Aktivitas Kelas Bahasa Inggris di Sekolah Dasar Berdasarkan Pendekatan "Whole Language" - Edi Trisno (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2000)
This article discusses activities of the lessons that can be done in the classrooms to teach English as a local content at Elementary Schools in West Sumatera based on whole language approach and philosophy. The lessons should be proceeded from whole to parts, learner centered, meaningful for the students now, engage groups in social interaction, develop both oral and written language, and show faith in the learners expand their potential. The activites use literature based materials that provide learning through meaningful interaction by interconnecting of four language skills or modes of communication- Ilistening, speaking, reading, and writing. The skills are taught in context, the materials are organized and studied arround theme. There are group, paired, and independent activities for the students to achieve the objective.